Pro WPF and Silverlight MVVM - McLean Hall, Gary (Apress, 2012)
This book was conceived from a need to explain the MVVM pattern and how it helps structure WPF and Silverlight applications. I had worked on a number of projects where these technologies were used but general best practices were ignored because no one had formally explained the MVVM pattern and how it compared to other patterns such MVP and MVC.